Remaining Service Life Struktur Conveyor B pada Tambang Batubara PT XYZ di Kabupaten Tanah Laut, Provinsi Kalimantan Selatan - Vaisal Gilang Adrian; Elfida Moralista; Noor Fauzi Isniarno (UNISBA Press, 2022)
Abstract. Material transportation activities in the mining industry require a tool that can move materials effectively, such as conveyor which made from carbon steel that are susceptible to oxidation due to environmental effect. The structure that made from carbon steel will occur the corrosion and the damage which will reduce the remaining useful life of the tools. The research was conducted with the aim of knowing the type of corrosion, corrosion control, and the remaining service life of the conveyor structure. The research methodology uses the method of reducing the thickness of the conveyor structure which is carried out with the help of the Ultrasonic Thickness Gauge TT 130. The research was conducted on a conveyor structure with a length of 90 meters which is divided into 3 segments with 25 test points. Corrosion that occurs in the conveyor structure is included in the type of prevalent corrosion. Corrosion control is carried out by the coating method where the primary coating is 5000 seaguard, the intermediate coating is with sherglass FF, and the top coating is with aliphatic acrylic modified polyurethane. The corrosion rate that occurs is in the range of 0.1650 mm/year – 0.3100 mm/year, based on the parameters of the relative corrosion resistance of steel, it is included in the good category. The remaining service life of the conveyor structure ranges from 5.96 years – 10.91 years, there are 8 test points or about 32% test points which are predicted to not reach the design life of 15 years. Abstrak. Kegiatan transportasi material dalam industri pertambangan menggunakan alat conveyor. Struktur conveyor berbahan dasar logam mengalami korosi akibat pengaruh lingkungan serta kerusakan yang akan menyebabkan sisa umur pakai menjadi rendah. Penelitian dilakukan dengan tujuan untuk mengetahui jenis korosi, metode pengendalian korosi, dan sisa umur pakai dari struktur conveyor. Metodologi penelitian menggunakan metode pengurangan ketebalan struktur conveyor yang dilakukan dengan bantuan alat Ultrasonic Thickness Gauge TT 130 untuk mengukur tebal aktualnya. Penelitian dilakukan pada struktur conveyor dengan panjang 90 meter yang terbagi kedalam 3 segmen dengan 25 test point. Korosi yang terjadi pada struktur conveyor termasuk kedalam jenis korosi merata. Pengendalian korosi dilakukan dengan metode coating sistem 3 layer dimana primer coating menggunakan seaguard 5000, intermediate coating menggunakan sherglass FF, dan top coating menggunakan aliphatic acrylic modified polyurethane. Laju korosi yang terjadi berkisar antara 0,1650 mm/tahun – 0,3100 mm/tahun, berdasarkan parameter ketahanan korosi relatif baja maka termasuk ke dalam kategori baik (good). Umur pakai struktur conveyor adalah 8 tahun, dimana sisa umur pakai struktur conveyor berkisar antara 5,96 tahun – 10,91 tahun, sehingga terdapat 8 test point atau sekitar 32% test point yang diprediksi tidak dapat mencapai umur desainnya yaitu 15 tahun.